Synthesis, Morphology and Thermal Decomposition of Schiff Base Derived from m-Hydroxybenzaldehyde and p-Aminobenzoic Acid - Li, Shun-Jiang; Cai, Yan-Hua (Asian Journal of Chemistry, 2011)
Schiff base derived from m-hydroxybenzaldehyde and p-aminobenzoic acid was synthesized using improved jet milling: rapid efficient reaction without environment pollution and wastes. The compound had been characterized by FT-IR, 1H NMR techniques. SEM showed the Schiff base was rodlike and the average length of the rodlike particles was 1.5 μm, the average width was 250 nm. Accordingly, the aspect ratio of the particles was 6. The thermal stability of Schiff base derived from m-hydroxybenzaldehyde and p-aminobenzoic acid was investigated by TGA thermal analyzer. The result showed that the Schiff base appeared the maximum decomposition rate from 225-300 ºC and the decomposition reached about 40 %.